Estimation of alternative wall insulating solutions using the method of technological network model “cutting out” junctions/Sienų šiltinimo alternatyvių sprendimų įvertinimas, taikant technologinio tinklinio modelio mazgų “išpjovimo” metodą - Janušaitis, Rytis (Journal of Civil Engineering and Management, 1998)
The article investigates the problem of the dwelling house wall insulation of many-variant decisions estimation. At present multi-criteria evaluation methods are used. They provide the formal algorithm of the final effective selection of solution. However, during the optimisation of the decisions it is expedient to analyse the efficiency of intermediate decisions and those influencing the final findings. With that end in view the author suggests the multi- criteria problem of the evaluations of the variant decision using the method or technological network model of “cutting out” junctions. The main points of this method are: – To cut out a comparable variant junction. Comparable variant junction is such a junction that contains at least two technological process variants. – To determine comparable partial processes to the junction. – To carry out a multi-criteria evaluation. – To eliminate non-rational variants from further calculations. – To pick out the most effective decision for the junction. From such decisions the complex process variants of wall insulation are made and multi-criteria evaluation is repeated. This method increases the abilities to raise the number of the partial alternative decisions for establishing the effectiveness ot the intermediate decisions, to receive and verify quickly final results of the decision evaluation and to decrease the amount of the calculations. “Cutting out” junction method can be used for estimating the decisions of building thermal renovation at the designing stage. Article in Lithuanian. First Published Online: 26 Jul 2012